The Ex-Prisoner's Dilemma : How Women Negotiate Competing Narratives of Reentry and Desistance - Leverentz, Andrea M., 1973- (Book collections on Project MUSE., 2014)
Drawing on repeated interviews with forty-nine women newly released from prison, Leverentz explores the conflicting messages these women receive about who they are and who they should be-from prison staff, workers at halfway houses and drug treatment programs, family members, and friends. These messages, she shows, shape the narratives the women create to explain their past records and guide their future behavior.